Paradiplomasi Menuju Kota Dunia: Studi Kasus Pemerintah Kota Makassar - Laode Muhamad Fathun (Indonesian Perspective, 2016)
The transformation of governance from centralized to decentralized opens the role of local governments to contribute in advancing national interests. The birth of the Regional Autonomy Law as a legal framework for local governments to pursue development goals by looking at a number of potentials they have. The role of local governments is not only becoming a local actor but also an international actor known as ‘paradiplomacy’. The example of paradiplomacy in international relations is initiating cooperation on foreign investment to attract foreign investors. Makassar is one city that has been implementing paradiplomacy to create a smart city in order to achive good governance characterized by integrity, accountability, and transparent. Therefore, due to the rapid progress of the information technology every single town and district as well as province should create IT-based smart city to create a public service that is more efficient and innovative. Keywords: Transformation of governance, paradiplomacy, investment, international relations, smart city, information technology